GREEN SYNTHESIS AND CHARACTERIZATION OF IRON NANOPARTICLES USING PHYLLANTHUS AMARUS LEAF EXTRACT AND THEIR APPLICATION IN CRYSTAL VIOLET DYE DEGRADATION - Nnanna Ibe, Franklin (Universitas Ngeri Malang, 2025)
The green synthesis of nanoparticles using plant extracts offers a sustainable and eco-friendly alternative to conventional chemical methods that often involve toxic reagents and high energy consumption. In this study, iron oxide nanoparticles (FeNPs) were synthesized using aqueous leaf extract of Phyllanthus amarus, a medicinal plant known for its rich phytochemical content. The biosynthesized FeNPs (PaFeNPs) were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), UV-Vis and Energy Dispersive X-ray (EDX) spectroscopy to confirm their formation, functionalization, and elemental composition. Phytochemical screening of the leaf extract revealed the presence of key biomolecules such as flavonoids, terpenoids, saponins, proteins, carbohydrates, and reducing sugars, which played critical roles in the reduction and stabilization of the nanoparticles. The photocatalytic efficiency of the synthesized PaFeNPs was evaluated by degrading crystal violet (CV) dye under both ultraviolet (UV) light and dark conditions. Under UV exposure, significant dye degradation was observed, attributed to the generation of hydroxyl and superoxide radicals, while in the dark, dye removal was primarily due to adsorption. The color change from purple to nearly colorless confirmed effective CV removal in both conditions. These findings demonstrate that P. amarus-mediated FeNPs possess excellent photocatalytic and adsorptive properties, highlighting their potential application in environmental remediation. This study not only confirms the feasibility of using Phyllanthus amarus for the green synthesis of FeNPs but also suggests their potential for wastewater treatment applications, thereby contributing to sustainable nanotechnology and environmental protection.